Early West Tibetan Buddhist Monuments: Architecture, Art, History and Texts (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
This volume contains sixteen contributions devoted to historical monuments and materials relating to Western Tibet primarily between the late 9th and the 12th century. In one way or another, the thematic focus of all contributions is related to the establishment and spread of monastic Buddhism in the West Tibet kingdom, in particular the foundation of Buddhist monasteries and the role played by the state, the royal lineage and allied aristocratic clans. Studies of the sites of Nyarma and Tabo (both dating from 996), stelae, historiographical texts, including a genealogy of the royal lineage and the biography of one its most prominent representatives (the Royal Lama Yeshe ö, 947-1019), illustrated MSS and a fully decorated cave temple reflect the Buddhist rulers' and their aristocratic allies' vision of the West Tibetan kingdom.